Histology-Verified Intracranial Artery Calcification and Its Clinical Relevance With Cerebrovascular Disease - Du, Heng; Yang, Wenjie; Chen, Xiangyan (Frontiers in Neurology, 2022)
Intracranial artery calcification (IAC) was regarded as proxy for intracranial atherosclerosis (ICAS). IAC could be easily detected on routine CT brain, which was neglected by clinicians in the previous years. The evolution of advanced imaging technologies, especially the vessel wall scanning using high resolution-magnetic resonance imaging (HR-MRI), has aroused researchers’ interests to further explore the characteristics and clinical impacts of IAC. Recent histological evidence acquired from human cerebral artery specimens demonstrated that IAC could mainly involves two layers: the intima and the media. Accumulating evidence from histological and clinical imaging studies verified that intimal calcification is more associated with ICAS, while media calcification, especially the internal elastic lamina, contributes to arterial stiffness rather than ICAS. Considering the highly improved abilities of novel imaging technologies in differentiating intimal and media calcification within intracranial large arteries, this review aimed to describe the histological and imaging features of two types of IAC, as well as risk factors, the hemodynamic influences and other clinical impacts of IAC occurring in intimal or media layers.